PERILAKU KOMSUMSI BUAH DAN SAYUR ANAK SEKOLAH DASAR NEGERI 020583 BINJAI ESTATE - Irma Handayani (Jurnal Maternitas Kebidanan, 2019)
CONSUMPTION BEHAVIOR OF VEGETABLES AND VEGETABLES OF STATE ELEMENTARY SCHOOLS 020583 BINJAI ESTATE Irma Handayani Diploma Nursing Study Program, Healthy Nursing Academy Binjai, Indonesia email: handay1502@gmail.com ABSTRACT One of the balanced nutrition guidelines is adequate consumption of fruits and vegetables. Currently children aged 5-14 have a tendency to consume 20% of fruits and vegetables lower when compared to adults 30-59 years. The main problem arising from lack of fruit and vegetable consumption is calorie and protein deficiency disease (KKP), vitamin A deficiency (KVA), disorders due to iodine deficiency (IDD), and iron (Fe) deficiency anemia. The purpose of this study was to determine the consumption behavior of fruit and vegetables in children SDN 020583. This type of research is descriptive by using a cross sectional design. The population in this study was 38 people, the results of this study showed three domains of behavior, namely knowledge, attitudes, and actions, where good knowledge was 25 people (65.78%), enough as many as 12 people (31.57%) and less as many 1 person (2.63%), positive attitude as many as 37 people (97.36%) and those who have negative attitudes as much as 1 person (2.63), and who have actions in good fruit consumption as many as 32 people (84.21 %) and less as many as 6 people (15.78%), for actions in good vegetable consumption as many as 32 people (89.47%) and less than 4 people (10.52%).